(ØªØ·Ø¨ÙÙ Ø·Ø±ÙÙØ© Ø§ÙÙÙØ§Ø¹Ø¯Ù ÙØ§ÙØªØ±Ø¬Ù Ø© ÙØªØ±ÙÙØ©Ù Ù ÙØ§Ø±Ø© Ø§ÙØªØ¹Ø¨ÙØ± Ø§ÙØªØØ±ÙØ±ÙÙ (Ø¯Ø±Ø§Ø³Ø© Ù ØªØ¹Ø¯Ø¯Ø© Ø§ÙÙ ÙØ§ÙØ¹ ÙÙ ÙÙÙØ© Ø§ÙØªØ±Ø¨ÙØ©Ù ÙØ´Ø¹Ø¨Ø© ØªØ¹ÙÙÙ Ø§ÙÙØºØ©Ù Ø§ÙØ¹Ø±Ø¨ÙØ©Ù Ø¨Ø§ÙØ¬Ø§Ù Ø¹Ø©Ù Ø? - Manaf, Lutfi Abdul (Jurnal al Hikmah, 2016)
Tabir Tahriri is an Arabic writing learning skill in higher education, especially in Arabic Department. Actually, Tabir Tahriri learning is a common problem faced by Arabic students, Not only in the college, but also a common problem faced by students in the Middle East, one of which is in implementing the principles of nahwu and writing with insightful of reading and attention to arabic styles, a skill that is quite difficult to obtain. From these problems, Tabir Tahriri learning process was not separated from the use of Grammar and Translation method. Therefore, this research discusses about the implementation of Grammar and Translation method process to improve Tabir Tahriri skill which formulated in the formulation of the problem as follows: